EVALUATION OF DRUG MANAGEMENT AT THE CAMBA COMMUNITY HEALTH CENTER UPTD, MAROS DISTRICT, 202 - Firman, Imran; Alqadri, Dinar; Arifuddin, Adriana; Azis, Rahmawati (PT. Jurnal Center Indonesia Publisher, 2025)
Drug management is a series of pharmaceutical service activities involving aspects of planning, requesting, receiving, storing, distributing, controlling, recording, and reporting drugs. Drug management in CHCs is an important aspect because inefficiency will have a negative impact on health services. The purpose of this study was to evaluate drug management at the Camba Community Health Center UPTD so that it can be used as a reference material to improve the quality of drug management. This type of research is a non-experimental descriptive-observational study. The data used are data in the form of reports and documents on drug management at the community health center. The research instrument used an observation sheet with the references used being the Indonesian Minister of Health Regulation No. 74 of 2016 and the Indonesian Ministry of Health 2019 Technical Guidelines for Pharmaceutical Service Standards in CHCs. The results of the study indicate that drug management at the Camba Community Health Center UPTD is based on the Indonesian Minister of Health Regulation No. 74 of 2016 and the Indonesian Ministry of Health 2019 Technical Guidelines for Pharmaceutical Service Standards at CHCs in the planning aspect are included in the good category with a percentage value of 100%, the request aspect is 100% in the good category, the receipt aspect is 100% in the good category, the storage aspect is 87.5% in the good category, the distribution aspect is 66.7% in the sufficient category, the destruction and withdrawal aspect is 100% in the good category, the control aspect is 100% in the good category, the recording and reporting aspect is 100% in the good category. So it can be concluded that drug management at the Camba Community Health Center UPTD in 2024 has met the standards set by the Indonesian Ministry of Health.